Relationship between regulatory T cells subsets and lipid profile in dyslipidemic patients: a longitudinal study during atorvastatin treatment. Issue 1 (December 2016) - Guasti, Luigina; Maresca, Andrea; Schembri, Laura; Rasini, Emanuela; Dentali, Francesco; Squizzato, Alessandro; Klersy, Catherine; Robustelli Test, Laura; Mongiardi, Christian; Campiotti, Leonardo; Ageno, Walter; Grandi, Anna; et al.
Abstract Background The CD4+ T-lymphocytes and their subtype CD4 + CD25high FoxP3+ regulatory T cells are receiving growing interest as major regulators of atherogenesis. We sought to investigate 1) whether the CD4 + cell subsets were expressed differently in dyslipidemic patients (Pts) and healthy subjects (HS) and 2) whether atorvastatin treatment could be associated in-vivo and in-vitro with cell changes in expression and functional response. Methods CD4+ subsets frequency (CD4 + CD25high FoxP3+, CD4 + CD25-FoxP3+) and mRNA expression for FoxP3, IL-10 and TGF-β were evaluated in 30 consecutive Pts at baseline and after a 3-month atorvastatin therapy, and in 17 HS. Results The % of CD4 + cells did not differ between HS and Pts. The % of CD4 + CD25high FoxP3+ was higher in Pts than HS and did not change during treatment. The CD4 + CD25-FoxP3+ cells were similar between the two groups and were lower in Pts at visit 2. Cytokine expression and FoxP3 did not differ in HS and Pts and no substantial change was observed during treatment. At visit 1, CD4 + CD25high FoxP3+ cells were significantly correlated with both total-cholesterol (r = 0.570, P = 0.0002), LDL-cholesterol (r = 0.715, P = 0.0001), Apolipoprotein B (r = 0.590, P = 0.0001). In-vitro atorvastatin (up to 5 μM) failed to induce any significant modulation of cell functions. Conclusion CD4 + CD25high FoxP3+ regulatory cells seem to be over-stimulated in the early pre-clinical phase of atherosclerosis and a relationship exists between their frequency and circulating lipids. A potential immuno-modulation by statin treatment is not achieved through a normalization in peripheral CD4 + cell subsets.